Early diagnostic evaluation of mandibular symmetry using orthopantomogram - Francesca Silvestrini-Biavati; Alessandro Ugolini; Nicola Laffi; Carola Canevello; Armando Silvestrini-Biavati (Wolters Kluwer Medknow Publications, 2014)
Aims: The aim of this research was to complete Habets's method on orthopantomogram, in order to measure mandibular symmetry horizontally and diagonally in mixed dentition as the first diagnostic evaluation. Settings and Design: Mixed dentition subjects were consecutively selected according to skeletal maturity. Materials and Methods: Inclusion criteria were: Mixed dentition, cervical vertebral stages 1-2, Class II or Class III malocclusions, with or without unilateral posterior cross-bite. Fourteen subjects with cross-bite (mean age 8 y, 9 m) cross group (CG) and 14 subjects with normal transverse occlusion (mean age 8y, 6m) non-cross group (NCG) were selected. Nine measurements were determined. An asymmetry index was performed for all linear variables. Statistical Analysis Used: NCG patients' data were compared with CG data using parametric t-tests. Probabilities of <0.05 were accepted as significant. Results: In CG, comparing right and left side, single values showed no significant differences up to 6% (twice if compared to the 3% threshold value). T-tests showed statistically significant differences between the groups for ramus + condyle height (index 2.5% vs 4.5%, P = 0.04), condylar height (index 3.7% vs 6.6%, P = 0.02) and mandibular length (index 1.4% vs 2.3%, P = 0.04). Overall CG group was more asymmetrical than NCG. Conclusions: In mixed dentition (CS1-2), a first appraisal of mandibular symmetry may be performed on orthopantomogram utilizing this modified Habets's method. This tracing method provides an early evaluation about mandibular symmetry and is able to show slight asymmetries in mixed dentition thereby reducing the number of cone beam computed tomograms performed.